Effects of social intention on movement kinematics in cooperative actions - Quesque, Francois; Lewkowicz, Daniel; Delevoye-Turrell, Yvonne N.; Coello, Yann (Frontiers in Neurorobotics, 2013)
Optimal control models of biological movements are used to account for those internal variables that constrain voluntary goal-directed actions. They however do not take into account external environmental constraints as those associated to social intention. We investigated here the effects of the social context on kinematic characteristics of sequential actions consisting in placing an object on an initial pad (preparatory action) before reaching and grasping as fast as possible the object to move it to another location (main action). Reach-to-grasp actions were performed either in an isolated condition or in the presence of a partner (audience effect), located in the near or far space (effect of shared reachable space), and who could intervene on the object in a systematic fashion (effect of social intention effect) or not (effect of social uncertainty). Results showed an absence of audience effect but nevertheless an influence of the social context both on the main and the preparatory actions. In particular, a “localized” effect of shared reachable space was observed on the main action, which was smoother when performed within the reachable space of the partner. Furthermore, a “global” effect of social uncertainty was observed on both actions with faster and jerkier movements. Finally, social intention affected the preparatory action with higher wrist displacements and slower movements when the object was placed for the partner rather than placed for self-use. Overall, these results demonstrate specific effects of action space, social uncertainty and social intention on the planning of reach-to-grasp actions, in particular on the preparatory action, which was performed with no specific execution constraint. These findings underline the importance of considering the social context in optimal models of action control for human-robot interactions, in particular when focusing on the implementation of motor parameters required to afford intuitive interactions.